High-hardness wear-resistant antifriction coating applied to high-speed cutting tool and preparation method of high-hardness wear-resistant antifriction coating
By introducing Mo elements into the AlTiN coating, AlTiMoN coating was prepared, which solved the problem of high friction coefficient of the coating during high-speed cutting, and achieved the optimization of hardness improvement and friction wear performance. It was suitable for high-speed cutting tools.
Patent Information
- Application Number
- CN202411719137.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-02-28
AI Technical Summary
The friction coefficient of the existing AlTiN coating is too high during high-speed cutting, resulting in tool temperature increase and wear acceleration, affecting service life.
The AlTiMoN coating is adopted, including the AlTiMoN layer at the upper end and the Ti layer at the lower end. The Al atom ratio is 20-25%, the Ti atom ratio is 10-15%, the Mo atom ratio is 4-6%, and the N atom ratio is 55-65%. It is prepared by titanium ion cleaning, deposition of Ti base layer and AlTiMoN layer.
The hardness and friction wear performance of the coating are significantly improved, the friction coefficient is reduced to less than 0.5, the wear rate is less than 3×10-6mm3/(N·m), and the bonding force with the substrate is good, suitable for high-speed cutting applications.
Smart Images

Figure CN119530709A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of coating materials, and in particular to a high-hardness, wear-resistant and friction-reducing coating used for high-speed cutting tools and a preparation method thereof. Background Art
[0002] As a hard protective coating, metal nitride coating is widely used in industry. Among them, TiN coating is the first generation of metal nitride coating, which is often used on various tool materials. However, due to the limited mechanical and tribological properties of TiN coating, this coating is gradually replaced by other coatings.
[0003] In the prior art, Al elements are added to TiN coatings to form AlTiN coatings, which have significantly improved properties such as hardness, wear resistance, thermal stability and oxidation resistance, and the coating hardness can be increased to more than 25GPa. In addition, since a dense Al2O3 layer is formed during the friction process, the wear resistance and oxidation resistance are significantly improved compared to TiN coatings, and the friction coefficient is reduced. At high temperatures, AlTiN coatings can maintain a stable single-phase cubic structure, and the coating has high thermal stability, so it is suitable for high-speed cutting operations.
[0004] However, the friction coefficient of the coating is very high, higher than 0.7. During the cutting process, the high friction coefficient will cause the tool temperature to rise, accelerate the tool wear process, and be detrimental to the tool life.
[0005] Therefore, in order to further improve its friction coefficient, the present invention proposes a high-hardness, wear-resistant and friction-reducing coating for high-speed cutting tools and a preparation method thereof. Summary of the invention
[0006] The purpose of the present invention is to provide a high-hardness wear-resistant and friction-reducing coating for high-speed cutting tools and a preparation method thereof, so as to solve the problems in the background technology.
[0007] To achieve the above-mentioned object, the present invention provides a high-hardness, wear-resistant and friction-reducing coating for high-speed cutting tools, comprising an AlTiMoN layer at an upper end and a Ti layer at a lower end, wherein the AlTiMoN layer contains 20 to 25% Al atoms, 10 to 15% Ti atoms, 4 to 6% Mo atoms, and 55 to 65% N atoms.
[0008] Preferably, the ratio of Mo atoms is 10-15% of the total number of aluminum, titanium and molybdenum atoms.
[0009] The present invention also provides a method for preparing the high-hardness, wear-resistant and friction-reducing coating for high-speed cutting tools, comprising the following steps:
[0010] S1, titanium ion cleaning: select the substrate and place it on the sample holder, then place it in the vacuum chamber. After heating, control the vacuum degree of the vacuum chamber to 7×10 -3 ~9×10 -3 Pa, introduce Ar, adjust the gas pressure and then turn on the Ti target power supply to perform titanium ion cleaning;
[0011] S2, depositing Ti as a base layer: after completing the titanium ion cleaning, reducing the bias voltage of the Ti target power supply, and depositing the Ti layer;
[0012] S3, deposition of AlTiMoN layer: After the Ti layer is deposited, Al 60 Ti 30 Mo 10 The target is prepared by introducing N2 and Ar at the same time. After adjusting the gas pressure, the power supply of the AlTiMo target is turned on. After the deposition is completed, a high-hardness, wear-resistant and friction-reducing coating is obtained.
[0013] Preferably, in S1, the vacuum chamber is heated to 350-400°C, the gas pressure is 0.2-0.5 Pa, the bias voltage of the Ti target power supply is -800V--1000V, and the cleaning time of titanium ions is 3-5 minutes.
[0014] Preferably, in S1, the vacuum chamber is heated to 350°C, the bias voltage of the Ti target power supply is -1000V, and the cleaning time of the titanium ions is 3 minutes.
[0015] Preferably, in S2, the bias voltage is -300V to -400V, the target current is controlled to be 60 to 80A, the deposition time is 25 to 35min, and the deposition thickness of the Ti layer is 200 to 400nm.
[0016] Preferably, in S2, the bias voltage is -300 V, the target current is controlled to be 80 A, and the deposition time is 25 min.
[0017] Preferably, in S3, the flow ratio of N2 to Ar gas is 8:1-10:1, and the gas pressure is adjusted to 0.5-3.0 Pa.
[0018] Preferably, in S3, the bias voltage is -100V to -200V, the target current is 60 to 80A, the deposition time is 120 to 180min, and the thickness of the AlTiMoN layer is 2.0 to 3.0 μm.
[0019] Preferably, in S3, the bias voltage is -100 V, the target current is 80 A, and the deposition time is 120 min.
[0020] Preferably, the high-hardness wear-resistant and friction-reducing coating prepared by the above preparation method has a hardness greater than 30 GPa, a film-base bonding force greater than 65 N, and a wear rate less than 3×10 -6 mm 3 / (N·m), the friction coefficient is less than 0.5.
[0021] Preferably, the prepared high-hardness, wear-resistant and friction-reducing coating is applied in the field of surface protective coatings for high-speed cutting tools.
[0022] Therefore, the high-hardness wear-resistant and friction-reducing coating for high-speed cutting tools and the preparation method thereof of the present invention have the following beneficial effects:
[0023] (1) In the present invention, the AlTiMoN coating is used, and the doped Mo atoms replace part of the Ti atoms in the (Al, Ti)N phase in the AlTiN coating, thereby producing a solid solution strengthening effect, which helps to improve the hardness of the coating.
[0024] (2) After adding the Mo element, the coating hardness can be improved by generating a harder Mo2N phase. During the friction, wear and cutting process, the Mo2N phase is heated to generate the oxide MoO3, which belongs to the Magnéli phase and has a certain self-lubricating effect during friction. It can effectively reduce the friction coefficient of the coating, thereby reducing wear and improving the friction and wear performance and cutting performance of the coating.
[0025] (3) The multi-metal nitride coating system prepared by the present invention has high hardness, good bonding strength with the substrate, and excellent wear resistance and friction reduction performance. It has the advantages of low wear rate and low friction coefficient, and can be well applied to fields such as high-speed cutting tools.
[0026] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is a SEM morphology image of Example 1 of the present invention, wherein a is the surface morphology and b is the cross-sectional morphology;
[0028] Figure 2 is the XRD pattern of Example 1 of the present invention;
[0029] Figure 3 This is a scratch comparison diagram of Example 1, Comparative Example 1 and Comparative Example 2 of the present invention, wherein a is Example 1, b is Comparative Example 1, and c is Comparative Example 2;
[0030] Figure 4 1 is a comparison chart of cutting performance between Example 1 of the present invention and Comparative Example 1, wherein (a) is Example 1 and (b) is Comparative Example 1;
[0031] Figure 5 It is a comparison diagram of the friction coefficient curves and wear rates of Example 1, Comparative Example 1 and Comparative Example 2 of the present invention, wherein a is the friction coefficient curve and b is the wear rate. DETAILED DESCRIPTION
[0032] The technical solution of the present invention is further described below through the accompanying drawings and embodiments.
[0033] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments.
[0034] Example 1
[0035] This embodiment provides a high-hardness, wear-resistant and friction-reducing coating, which includes an AlTiMoN layer and a Ti base layer from top to bottom. The atomic percentage content of each element in the coating is: Al atomic ratio 20.8%, Ti atomic ratio 12.5%, Mo atomic ratio 5.1%, N atomic ratio 61.6%, among which Mo / (Al+Ti+Mo)=13.3%.
[0036] The preparation method is as follows:
[0037] S1. Select cemented carbide YG8 as the substrate, put the substrate into acetone and alcohol for ultrasonic cleaning respectively, and install it on the sample holder after cleaning and drying;
[0038] Place the sample holder in the vacuum chamber, close the door and evacuate the chamber, and at the same time, raise the temperature to 350°C. Wait until the vacuum chamber pressure reaches 9×10 -3 Pa, introduce Ar gas, maintain the gas pressure at 0.5Pa, turn on the Ti target power supply, select the bias voltage of -1000V, and the cleaning time is 3min;
[0039] S2, depositing a transition layer Ti layer: the bias voltage of the Ti target power supply is selected to be -300 V, the current is selected to be 80 A, and the deposition time is 25 min; a Ti transition layer with a thickness of about 320 nm is deposited;
[0040] S3, deposition of AlTiMoN layer: nitrogen and argon are introduced at the same time, and the flow ratio is controlled to be 8:1; the gas pressure is controlled at about 0.5Pa, and only Al is opened. 60 Ti 30 Mo 10 The target power supply, bias voltage is -100V, current is 80A, and deposition time is 120min; an AlTiMoN layer with a thickness of about 2.4μm is deposited;
[0041] After coating is completed, turn off the power and gas, and take out the sample holder when the temperature drops to about 50°C.
[0042] The above coatings were subjected to morphology inspection and performance testing. The surface morphology and cross-sectional morphology were as follows: Figure 1As shown in the figure, the coating properties are as follows: hardness 32.1GPa; the bonding force between the coating and the substrate is 68N; the wear rate is 1.9×10 -6 mm 3 / (N·m); friction coefficient is about 0.45. XRD test is performed on the above coating, such as Figure 2 As shown in the figure, the analysis shows that in addition to the (Al, Ti) N phase, the Mo2N phase is also generated in the prepared AlTiMoN coating; the diffraction peak position of the (Al, Ti) N phase has shifted to a certain extent, indicating that Mo atoms have replaced some Ti atoms in the (Al, Ti) N phase; the formation of the harder Mo2N phase in the coating and the solid solution strengthening caused by the replacement of Mo atoms are conducive to the improvement of the hardness of the AlTiMoN coating. In addition, the Mo2N phase will generate the MoO3 phase with a self-lubricating effect during the friction, wear and cutting process, which can effectively reduce the friction coefficient of the coating, thereby reducing wear, thereby improving the friction and wear performance and cutting performance of the coating.
[0043] Example 2
[0044] The present embodiment provides a high-hardness, wear-resistant and friction-reducing coating, which includes an AlTiMoN layer and a Ti layer from top to bottom. The atomic percentage content of each element in the coating is: the Al atomic ratio is 23.6%, the Ti atomic ratio is 10.8%, the Mo atomic ratio is 4.2%, and the N atomic ratio is 61.4%, wherein Mo / (Al+Ti+Mo)=10.9%.
[0045] The preparation method is as follows:
[0046] S1. Select cemented carbide YG8 as the substrate, put the substrate into acetone and alcohol for ultrasonic cleaning respectively, and install it on the sample holder after cleaning and drying;
[0047] Place the sample holder in the vacuum chamber, close the door and evacuate the chamber, and at the same time, raise the temperature to 400°C. Wait until the vacuum chamber pressure reaches 9×10 -3 Pa, introduce Ar gas, maintain the gas pressure at 0.5 Pa, turn on the Ti target power supply, select the bias voltage of -800 V, and the cleaning time is 5 minutes.
[0048] S2, depositing a transition layer Ti layer: the bias voltage of the Ti target power supply is selected to be -300 V, the current is selected to be 80 A, and the deposition time is 35 min; a Ti transition layer with a thickness of about 360 nm is deposited;
[0049] S3, deposition of AlTiMoN layer: nitrogen and argon are introduced at the same time, and the flow ratio is controlled to be 10:1; the gas pressure is controlled at about 3.0Pa, and only Al is opened. 60 Ti 30 Mo 10The target power supply, bias voltage is -200V, current is 80A, and deposition time is 180min; an AlTiMoN layer with a thickness of about 2.8μm is deposited;
[0050] After coating is completed, turn off the power and gas, and take out the sample holder when the temperature drops to about 50°C.
[0051] The performance of the coating was tested and the coating properties were as follows: hardness 30.1 GPa; the bonding force between the coating and the substrate 66 N; the wear rate 2.5 × 10 -6 mm 3 / (N·m); friction coefficient is about 0.48.
[0052] Comparative Example 1
[0053] This comparative example provides an AlTiN coating system, which includes an AlTiN layer and a Ti base layer from top to bottom. The atomic percentage content of each element in the coating is: Al atomic ratio 27.2%, Ti atomic ratio 15.8%, N atomic ratio 57.0%.
[0054] The preparation method is as follows:
[0055] S1. Select cemented carbide YG8 as the substrate, put the substrate into acetone and alcohol for ultrasonic cleaning respectively, and install it on the sample holder after cleaning and drying;
[0056] Place the sample holder in the vacuum chamber, close the door and evacuate the chamber, and at the same time, raise the temperature to 350°C. Wait until the vacuum chamber pressure reaches 9×10 -3 Pa, introduce Ar gas, maintain the gas pressure at 0.5 Pa, turn on the Ti target power supply, select the bias voltage of -1000 V, and the cleaning time is 3 min.
[0057] S2, depositing a transition layer Ti layer: the bias voltage of the Ti target power supply is selected to be -300 V, the current is selected to be 80 A, and the deposition time is 25 min; a Ti transition layer with a thickness of about 210 nm is deposited;
[0058] S3, deposition of AlTiN layer: nitrogen and argon are introduced at the same time, and the flow ratio is controlled to be 5:1; the gas pressure is controlled at about 0.5Pa, and only Al is opened. 67 Ti 33 The target power supply, bias voltage is -100V, current is 80A, and deposition time is 120min. The AlTiN layer with a thickness of about 3.3μm is deposited.
[0059] After coating is completed, turn off the power and gas, and take out the sample holder when the temperature drops to about 50°C.
[0060] The coating was tested for performance, and the coating performance was as follows: hardness 27.2GPa; wear rate 5.4×10-6 mm 3 / (N·m); friction coefficient is about 0.80.
[0061] Comparative Example 2
[0062] This comparative example provides an AlTiMoN coating system, which includes an AlTiMoN layer and a Ti base layer from top to bottom, and the atomic percentage content of each element in the coating is: Al atomic ratio 20.4%, Ti atomic ratio 10.3%, Mo atomic ratio 3.3%, N atomic ratio 66.0%, wherein Mo / (Al+Ti+Mo)=9.7%.
[0063] The preparation method is as follows:
[0064] (1) Select cemented carbide YG8 as the substrate, put the substrate into acetone and alcohol for ultrasonic cleaning, and after cleaning and drying, install it on the sample holder;
[0065] Place the sample holder in the vacuum chamber, close the door and evacuate the chamber, and at the same time, raise the temperature to 200°C. Wait until the vacuum chamber pressure reaches 9×10 -3 Pa, introduce Ar gas, maintain the gas pressure at 0.5 Pa, turn on the Ti target power supply, select the bias voltage of -800 V, and the cleaning time is 5 minutes.
[0066] (2) Deposition of transition layer Ti layer: The bias voltage of the Ti target power supply is -400 V, the current is 60 A, and the deposition time is 30 minutes; a Ti transition layer with a thickness of about 300 nm is deposited;
[0067] (3) Deposition of AlTiMoN layer: nitrogen and argon were introduced simultaneously, and the flow ratio was controlled to be 5:1; the gas pressure was controlled to be around 2.0 Pa, only the Al60Ti30Mo10 target power supply was turned on, the bias voltage was selected to be -100 V, the current was selected to be 60 A, and the deposition time was 120 minutes; an AlTiMoN layer with a thickness of about 2.0 μm was deposited;
[0068] After coating is completed, turn off the power and gas, and take out the sample holder when the temperature drops to about 50°C.
[0069] The performance of the coating was tested and the coating properties were as follows: hardness 27.5 GPa; the bonding force between the coating and the substrate was 66 N; the wear rate was 3.8 × 10 -6 mm 3 / (N·m); friction coefficient is about 0.55;
[0070] The coating in Example 1, the coating in Comparative Example 1 and the coating in Comparative Example 2 were subjected to scratch test, cutting performance test and friction test respectively. Figure 3As shown, after analysis and calculation, it is obtained that the bonding strength between the AlTiMoN coating of Example 1 and the substrate is 68N, while the bonding strength between the AlTiN coating of Comparative Example 1 and the substrate is 63N, and the bonding strength between the AlTiMoN coating of Comparative Example 2 and the substrate is 66N, indicating that the bonding strength between the AlTiMoN coating and the substrate is better, and the bonding strength between the AlTiMoN coating of Example 1 and the substrate is better than that of the AlTiMoN coating of Comparative Example 2.
[0071] The cutting performance comparison diagram of Example 1 and Comparative Example 1 is as follows: Figure 4 As shown, it can be seen that the cutting force and cutting temperature of the tool coated with AlTiMoN coating during the cutting process are significantly lower than those of the tool coated with AlTiN coating, indicating that the cutting performance of AlTiMoN coating is better than that of AlTiN.
[0072] The friction coefficient curves and wear rates of Example 1, Comparative Example 1 and Comparative Example 2 are as follows: Figure 5 As shown, the results show that the friction coefficient and wear rate of the AlTiMoN coating are significantly lower than those of the AlTiN coating, that is, the friction and wear performance of the AlTiMoN coating is better than that of AlTiN; in addition, the friction and wear performance of the AlTiMoN coating of Example 1 is better than that of the AlTiMoN coating of Comparative Example 2.
[0073] In summary, after adding the Mo element to the AlTiN coating of Comparative Example 1, the comprehensive performance of the AlTiMoN coating is obviously better than that of the AlTiN coating due to the addition of the Mo element. In addition, the comprehensive performance of the AlTiMoN coating of Example 1 is better than that of the AlTiMoN coating in Comparative Example 2. The process parameters in Comparative Example 2 have not been optimized, especially the atmosphere ratio during the preparation process. The atmosphere ratio of nitrogen to argon will affect the composition of the prepared AlTiMoN coating. The present invention limits the gas flow ratio of N2 to Ar to 8:1 to 10:1, and a coating with better performance can be obtained within this range; secondly, the Mo content in the AlTiMoN coating will significantly affect the comprehensive performance of the coating. The present invention limits the Mo atomic ratio to 4-6% by adjusting the process parameters of the deposition process, and the Mo atomic ratio is 10-15% of the total number of aluminum, titanium and molybdenum atoms, which can significantly improve the comprehensive performance of the AlTiMoN coating.
[0074] Therefore, the present invention provides a high-hardness, wear-resistant and friction-reducing coating for high-speed cutting tools and a preparation method thereof. The prepared coating system has high hardness, good bonding strength with the substrate, excellent wear-resistant and friction-reducing properties, and can effectively improve the cutting performance of the turning tool during cutting.
[0075] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.
Claims
1. A high-hardness, wear-resistant and friction-reducing coating for high-speed cutting tools, characterized in that: It comprises an upper AlTiMoN layer and a lower Ti layer, wherein the AlTiMoN layer has an Al atomic ratio of 20-25%, a Ti atomic ratio of 10-15%, a Mo atomic ratio of 4-6%, and a N atomic ratio of 55-65%.
2. The high-hardness, wear-resistant and friction-reducing coating for high-speed cutting tools according to claim 1, characterized in that: The ratio of the Mo atoms is 10-15% of the total number of aluminum, titanium and molybdenum atoms.
3. A method for preparing a high-hardness, wear-resistant and friction-reducing coating for high-speed cutting tools according to any one of claims 1 to 2, characterized in that: The steps include: S1, titanium ion cleaning: select the substrate and place it on the sample holder, then place it in the vacuum chamber. After heating, control the vacuum degree of the vacuum chamber to 7×10 -3 ~9×10 -3 Pa, introduce Ar, adjust the gas pressure and then turn on the Ti target power supply to perform titanium ion cleaning; S2, depositing Ti as a base layer: after completing the titanium ion cleaning, reducing the bias voltage of the Ti target power supply, and depositing the Ti layer; S3, deposition of AlTiMoN layer: After the Ti layer is deposited, Al 60 Ti 30 Mo 10 The target is prepared by introducing N2 and Ar at the same time. After adjusting the gas pressure, the power supply of the AlTiMo target is turned on. After the deposition is completed, a high-hardness, wear-resistant and friction-reducing coating is obtained.
4. The method for preparing a high-hardness, wear-resistant and friction-reducing coating for high-speed cutting tools according to claim 3, characterized in that: In S1, the vacuum chamber is heated to 350-400°C, the gas pressure is 0.2-0.5 Pa, the bias voltage of the Ti target power supply is -800V--1000V, and the cleaning time of titanium ions is 3-5 minutes.
5. The method for preparing a high-hardness, wear-resistant and friction-reducing coating for high-speed cutting tools according to claim 3, characterized in that: In S1, the vacuum chamber is heated to 350°C, the bias voltage of the Ti target power supply is -1000V, and the cleaning time of titanium ions is 3 minutes.
6. The method for preparing a high-hardness, wear-resistant and friction-reducing coating for high-speed cutting tools according to claim 3, characterized in that: In the S2, the bias voltage is -300V to -400V, the target current is controlled to be 60 to 80A, the deposition time is 25 to 35min, and the deposition thickness of the Ti layer is 200 to 400nm.
7. The method for preparing a high-hardness, wear-resistant and friction-reducing coating for high-speed cutting tools according to claim 3, characterized in that: In S2, the bias voltage is -300 V, the target current is controlled to be 80 A, and the deposition time is 25 min.
8. The method for preparing a high-hardness, wear-resistant and friction-reducing coating for high-speed cutting tools according to claim 3, characterized in that: In the S3, the flow ratio of N2 to Ar gas is 8:1-10:1, and the gas pressure is adjusted to 0.5-3.0Pa.
9. The method for preparing a high-hardness, wear-resistant and friction-reducing coating for high-speed cutting tools according to claim 3, characterized in that: In the S3, the bias voltage is -100V to -200V, the target current is 60 to 80A, the deposition time is 120 to 180min, and the thickness of the AlTiMoN layer is 2.0 to 3.0μm.
10. The method for preparing a high-hardness, wear-resistant and friction-reducing coating for high-speed cutting tools according to claim 3, characterized in that: In S3, the bias voltage is -100 V, the target current is 80 A, and the deposition time is 120 min.